The Use of Guided Inquiry Approach to Improve Class X Students’ Physics Problem Solving Skills at SMA 1 Watampone Kabupaten Bone - A. Muafiah Nur (Jurnal Pendidikan Fisika, 2019)
This research is a pre-experimental that aims to know: 1) measuring students’ ability of tenth grade SMA Negeri 1 Watampone in solving physics problem that is taught by using guided inquiry approach, 2) measuring the students’ ability in solving physics problem through guided inquiry approach achieve the level of Minimum Passing Standard. The population and all at once as sample in this research is 36 or all of student at tenth grade SMA Negeri 1 Watampone in 2016/2017 academic year. The research design used in this research is One Shot Case Study. The research instrument is the description test in solving physics problem. The result of descriptive analysis shows that the average score of students’ physics achievement after taugh by using guided inquiry approach is 108 and 12 for standard deviation. While the result of inferential analysis shows that students’ ability achieve the minimum passing standard at significance level α = 0,05.Keywords: guided approach; problem solving skills; Descriptive statistics; inferential statisticsPenelitian ini adalah penelitian pra eksprimen yang bertujuan untuk: (1) mengetahui besarnya kemampuan siswa kelas X SMA Negeri 1 Watampone dalam memecahkan masalah fisika yang diajar dengan menggunakan pendekatan inkuiri terbimbing, (2) mengetahui kemampuan siswa kelas X SMA Negeri 1 Watampone dalam memecahkan masalah fisika melalui pendekatan inkuiri terbimbing mencapai tingkat Kriteria Ketuntasan Minimal. Subjek populasi sekaligus sebagai sampel dalam penelitian ini adalah seluruh siswa kelas X SMA Negeri 1 Watampone tahun pelajaran 2016/2017 sebanyak 36 siswa. Desain Penelitian yang digunakan adalah One Shot Case Study. Instrumen penelitian yang digunakan adalah tes kemampuan memecahkan masalah fisika dalam bentuk tes uraian. Hasil analisis deskriptif menunjukkan skor rata-rata hasil belajar fisika siswa kelas X SMA Negeri 1 Watampone setelah diajar dengan pendekatan inkuiri terbimbing sebesar 108 dan standar deviasi 12. Hasil analisis inferensial menunjukkan bahwa kemampuan siswa kelas X SMA Negeri 1 Watampone dalam memecahkan masalah fisika setelah diajar dengan pendekatan inkuiri terbimbing pada pembelajaran fisika mencapai tingkat Kriteria Ketuntasan Minimal pada taraf nyata α = 0,05.Kata kunci: pendekatan ikuiri terbimbing; kemampuan memecahkan masalah; statistik deskriptif; statistik inferensial